Financing the alternative: renewable energy in developing and transition countries - Christa N. Brunnschweiler (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
This paper examines the determinants of credit allocation to renewable energy firms in developing and transition countries. Using a simple en- dogenous growth model, we show that the development of the renewable energy sector, i.e. the diversification of renewable energy resources used in primary energy production, depends on the quality of financial intermedia- tion, debtor information costs to banks, and financing needs of renewable energy firms. Policies should aim at increasing financial sector perfor- mance through better institutional frameworks and improving financing conditions for new energy firms. The empirical analysis confirms the pos- itive effect of financial intermediary development on the renewable energy sector.
Keywords: Q42; G10; O41; 330; Financial intermediation; banks; renewable energy; economic growth; Unternehmensfinanzierung; Erneuerbare Energie; Kreditwürdigkeit; Finanzintermediation; Endogenes Wachstumsmodell; Entwicklungsländer